Proses Pengujian Berat Pada Baja Tulangan Polos (BJTP) - Muhammad Aji Badiuz Zaman (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Plain reinforcing steel bars are one of the important components in reinforced concrete structures, particularly in non-structural elements that do not receive significant tensile loads. To ensure quality and compliance with technical standards such as SNI 2052:2017, weight testing is required to determine the mass per meter length of the steel bars. The Industrial Laboratory Service Unit of Tegal Regency plays a role in conducting this testing as part of construction material quality control. This study aims to comprehensively review the stages and procedures of weight testing for plain reinforcing steel bars carried out in the laboratory, starting from sample collection to the processing of test result data. The accuracy of the results is strongly influenced by factors such as equipment calibration, sample condition, and the precision of the testing personnel. Therefore, the implementation of standard operating procedures and the use of appropriate equipment are crucial aspects in ensuring the validity of test results. This study is expected to serve as a reference for industry practitioners, academics, and related stakeholders in efforts to improve construction quality and safety. Keywords: Plain reinforcing steel bars, weight testing, material quality, SNI 2052:2017 standard, laboratory Abstrak Baja tulangan polos merupakan salah satu komponen penting dalam struktur beton bertulang, terutama pada bagian non-struktural yang tidak menerima beban tarik signifikan. Untuk menjamin mutu dan kesesuaian dengan standar teknis seperti SNI 2052-2017, diperlukan pengujian berat guna mengetahui massa jenis per meter panjang baja tersebut. UPT Laboratorium Perindustrian Kabupaten Tegal berperan dalam melakukan pengujian ini sebagai bagian dari pengawasan mutu material konstruksi. Kajian ini bertujuan untuk mengulas secara mendalam tahapan dan prosedur pengujian berat baja tulangan polos di laboratorium tersebut, mulai dari pengambilan sampel hingga pengolahan data hasil uji. Keakuratan hasil sangat dipengaruhi oleh faktor-faktor seperti kalibrasi alat, kondisi sampel, serta ketelitian pelaksana uji. Oleh karena itu, penerapan prosedur operasional standar dan penggunaan peralatan yang sesuai menjadi aspek krusial dalam menjamin validitas hasil uji. Penelitian ini diharapkan dapat menjadi referensi bagi pelaku industri, akademisi, dan pihak terkait dalam upaya meningkatkan mutu dan keselamatan konstruksi. Kata Kunci: Baja tulangan polos, pengujian berat, mutu material, standar SNI 2052:2017, laboratorium